A Contextual Analysis and Critical Examination of e-Government as a Form of Public Accountability and Equitable Public Service Delivery - Nanda Widaninggar; Lita Permata Sari; Muhammad Firdaus; Yulia Variska Putri (E-Jurnal Akuntansi, 2025)
The purpose of this study is to critically analyze and contextualize the implementation of e-government in Situbondo Regency. E-government is adopted by the government with the belief that it can strengthen public accountability and enhance the distribution of public services. However, a significant portion of citizens remains unable to access egovernment services. The research uses a contextual analysis approach combined with in-depth interviews to explore key ideas relevant to the analysis. The bureaucratic reform in the public policy system lacks humanistic values, diminishes the spirit of public service, and does not reflect good governance. E-government, while seen as a technological revolution, faces the challenge of the digital divide, which silences citizens' rights due to a lack of digital literacy. As a result, public accountability is not effectively established through e-government.